The Distribution of Stroma and Antral Follicles Differs between Insulin-Resistance and Hyperandrogenism-Related Polycystic Ovarian Syndrome - Alviggi, Carlo; Conforti, Alessandro; De Rosa, Pasquale; Strina, Ida; Palomba, Stefano; Vallone, Roberta; Gizzo, Salvatore; Borrelli, Rosaria; Andersen, Claus Yding; De Placido, Giuseppe; Guerriero, Stefano (Frontiers in Endocrinology, 2017)
Introduction. Although insulin resistance plays an important pathogenetic role in PCOS, no correlation between ultrasound PCOS pattern and insulin resistance has yet been reported. The aim of this retrospective observational study was to assess the impact of insulin resistance on ovarian ultrasonographic parameters in patients with PCOS. Materials and Methods. Women who fulfilled the Rotterdam criteria for PCOS were retrospectively studied. Anthropometric, biochemical and clinical data were recorded. Women were divided into two groups based on specific transvaginal ultrasound parameters: subjects with more than half of follicles measuring between 5 and 9 mm in diameter, an ultrasonographic determined stroma/total area (S/A) > 0.34 and a “necklace” sign of antral follicles (Group A); and subjects with more than half of antral follicles measuring between 2 and 4 mm in diameter, an S/A ≤ 0.34; no "necklace" sign but ubiquitously distributed follicles determined by ultrasound (Group B). The association between these ultrasound patterns and the presence of insulin resistance was also evaluated. Results. Seventy-eight patients were enrolled: 33 with ultrasound sound pattern A and 45 with pattern B. The latter pattern had a sensitivity of 88% and a specificity of 78% in predicting PCOS women with insulin resistance. There were no differences in age, Ferriman-Gallwey score and serum gonadotropin or androgen levels between the two groups. Body mass index, the waist-to-hip ratio and homeostasis model assessment were significantly higher in group B than in group A (p < 0.05). Conversely, sex hormone binding globulin levels and ovarian volume were significantly higher in group A (p < 0.05). Insulin resistance was more frequent in group B than in group A (36/41, 87.8% versus 7/32, 21.8%; p < 0.05). Conclusion. These results suggest that insulin resistance could be associated with a specific ultrasound pattern in PCOS patients.